Individuals’ preference on reading pathways influences the involvement of neural pathways in phonological learning - Dong, Jie; Yue, Qingxin; Li, Aqian; Gu, Lala; Su, Xinqi; Chen, Qi; Mei, Leilei (Frontiers in Psychology, 2022)
Existing behavioral and neuroimaging studies revealed inter-individual variability in the selection of the two phonological routes in word reading. However, it is not clear how individuals’ preferred reading pathways/strategies modulate the involvement of a certain brain region for phonological learning in a new language, and consequently affect their behavioral performance on phonological access. To address this question, the present study recruited a group of native Chinese speakers to learn two sets of artificial language characters respectively in addressed-phonology training (i.e., whole-word mapping) and assemble-phonology training conditions (i.e., grapheme-to-phoneme mapping). Behavioral results showed that the more lexical pathways participants preferred, the better they performed on newly-acquired addressed characters relative to assembled characters. More importantly, neuroimaging results showed that participants who preferred lexical pathway in phonological access show less involvement of brain regions for addressed phonology (e.g., the bilateral orbitofrontal cortex and right pars triangularis) in the processing of newly-acquired addressed characters. These results indicated that phonological access via the preferred pathway required less neural resources to achieve better behavioral performance. These results provide direct neuroimaging evidence for the influence of reading pathway preference on phonological learning.